Large cervical mass and head and neck cancer. First report of ectopic papillary adenoma of the lung. (April 2022) - De Luca, Pietro; Di Stadio, Arianna; Tassone, Domenico; de Campora, Luca; Costarelli, Leopoldo; La Mantia, Ignazio; Camaioni, Angelo
Highlights: Masses of the neck are a common finding and have different causes. Identification of a mass in the neck is generally related to cancer in the head and neck area. Ectopic tissue in the neck can degenerate in rare cancer and misdiagnosed. A correct clinical approach allows a correct and safe diagnosis and correct management. Abstract: Aim: We aim to report the first case of ectopic papillary adenoma of the lung (PAL), identified in the neck. Methods: A 62-year-old woman with a known history of thyroid cancer treated several years ago, presented at our department because affected by an unpainful latero-cervical neck mass. The patient performed neck ultrasound echography, blood tests and computed tomography (CT) of head, neck and thorax to exclude the recurrence of the thyroid tumor or other unknown cancer of head and neck. Results: Her CT with contrast identified a large mass in the left thyroid loggia, with well-defined margins without post-contrast enhancement; the mass laterally displaced the trachea, without reduction of airways caliber. The tumor was removed. The histologic analysis showed aspects typical of PAL. Because the mass was completely removed, and no lymph nodes were identified, additional treatments were excluded. Conclusions: Despite the ectopic tissue can be rarely identified in the neck, it should be always considered because it might degenerate and cause, as in our case, a tumor like PAL. The diagnostic plan is fundamental to well manage latero-cervical mass avoiding risks for patients.